Amyloid β1‐40 Predicts Long‐Term Mortality Rate in Patients With Acute Myocardial Infarction - Aneta Aleksova; Alessandra Lucia Fluca; Alessandro Pierri; Giulia Barbati; Antonio Paolo Beltrami; Laura Padoan; Enzo Merro; Maria Marketou; Donna Zwas; Stefano D'Errico; Gianfranco Sinagra; Milijana Janjusevic (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Amyloid β1‐40 (Aβ1‐40) contributes to atherosclerosis, being involved in plaque formation and destabilization. The prognostic role of Aβ1‐40 in patients with acute myocardial infarction is currently limited to non–ST‐segment–elevation myocardial infarction (NSTEMI). We examined the prognostic value of Aβ1‐40 in a real‐world cohort of patients with acute myocardial infarction (both ST‐segment–elevation myocardial infarction [STEMI] and NSTEMI) and identified predictors for its elevated levels. Methods and Results Our population included 1119 consecutive patients (mean age, 67 years; 72% men; and STEMI, 68%). The median Aβ1‐40 concentration on admission was 86.9 (interquartile range, 54.5–128.9) pg/mL, and there was no difference in Aβ1‐40 levels between NSTEMI and STEMI (P=0.1). Higher Aβ1‐40 levels were predicted by older age, lower left ventricular ejection fraction, glycated hemoglobin >39 mmol/mol and glomerular filtration rate <60 mL/min per m2. From the final multivariable model, a nomogram was computed to determine probability of high Aβ1‐40. During the median follow‐up of 57 months, 193 patients (17.2%) died. Kaplan–Meier analysis revealed higher mortality risk in patients with Aβ1‐40 levels above the median (P<0.01), consistent across STEMI (P<0.01) and NSTEMI (P=0.01) subgroups. At Cox multivariable analysis including the entire cohort, Aβ1‐40 levels were predictive of death (hazard ratio, 1.03; P=0.01), together with older age, higher high‐sensitivity C‐reactive protein levels, smoking, glomerular filtration rate <60 mL/min per m2, worse left ventricular ejection fraction, and previous ischemic events. In the STEMI subcohort, Aβ1‐40 remained a significant predictor, along with advanced age, worse left ventricular ejection fraction, smoking, and elevated high‐sensitivity C‐reactive protein. No such association was found in patients with NSTEMI (P=0.17), likely due to the smaller cohort size and low event rate. Conclusions Aβ1‐40 is an independent predictor of death and improves risk stratification in patients with acute myocardial infarction.